Socio-Cultural Changes of Hananu Mate in the Death Song Bei Mate of The Tetun Tribe - Theresia Trivonia Sanan; Aton Rustandi Mulyana (Universitas Negeri Medan, 2025)
This study examines Hananu Mate , a traditional funeral song of the Tetun people of Timor, East Nusa Tenggara, within the context of the Bei Mate ceremony . As a form of oral expression, Hananu Mate not only expresses grief over the passing of a person but also contains the narrative of the deceased's life, social values, local spirituality, and the community's collective hopes. This study aims to uncover the narrative in Hananu Mate lyrics and the socio-cultural dynamics of the Tetun community as reflected in the changing form and meaning of the song in the modern era. This study uses a narrative approach based on Walter Fisher's narrative theory, which positions narrative as a primary form of human communication and a means of conveying collective values and meanings. In addition, social change theory as explained by Anthony Giddens and Inglehart-Baker is used to understand the cultural dynamics and transition of Hananu Mate's meaning in the context of modernizing Tetun society. The research method used is a qualitative approach with narrative ethnography techniques, in-depth interviews, participant observation, and lyrical text analysis. The findings indicate that Hananu Mate has a distinctive elegiac narrative structure, involving the flow of introducing the deceased, depicting social relations, spiritual reflection, and closing with hopes for future generations. This research confirms that Hananu Mate is a dynamic community narrative, continually transforming in response to modernization, education, and technological developments. Despite changes in form and meaning, this song continues to play a vital role in maintaining the cultural identity and continuity of Tetun social values.